Provably secure rational delegation computation protocol - Youliang TIAN; Qiuxian LI; Duo ZHANG; Linjie WANG (Tongxin xuebao)
A provably secure rational delegation computation scheme was proposed to solve the requirement of security issues in rational delegate computation.Firstly,game theory was introduced into delegation computation and according to rational participants behavior preferences analysis,a rational delegate computing game model was designed.Secondly,according to the equilibrium demand of game model and the security requirement of rational delegation computation,a rational security model was established.Thirdly,combining Yao's garbled circuit with its advantages of re-randomization,as well as full homomorphic encryption technology,the rational delegation computation protocol was constructed.And the combination of strategies in the protocol could reach the Nash equilibrium state.Finally,the security of the protocol and the privacy of the input and output were proved according to the rational security model,and the performance analysis shows the validity of the protocol.The proposed rational delegation computing protocol not only satisfies the traditional security,but also considers the behavioral preference of participants,which is more in line with the delegationcomputing mode under the big data environment.